2004
DOI: 10.1097/01.aog.0000113625.29073.4c
|View full text |Cite
|
Sign up to set email alerts
|

Singleton Vaginal Breech Delivery at Term

Abstract: II-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 24 publications
2
58
1
12
Order By: Relevance
“…The findings of this study prompted criticism of the analysis of the trial, highlighting that poor shortterm outcome variables do not have the predictive strength to surrogate for neonatal long-term development [24]. Authors of retrospective studies published in the following years reported excellent neonatal outcome after vaginal term deliveries in patients selected by strict criteria [6,25], without any differences in 5-minute Apgar scores, arterial cord blood pH, neonatal transfer rates [25], neurologic abnormalities [16] or infant mortality [26] between vaginal breech delivery and planned cesarean section. However, these data were derived from smaller samples [16,25,26] or from multicentric trials [6].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The findings of this study prompted criticism of the analysis of the trial, highlighting that poor shortterm outcome variables do not have the predictive strength to surrogate for neonatal long-term development [24]. Authors of retrospective studies published in the following years reported excellent neonatal outcome after vaginal term deliveries in patients selected by strict criteria [6,25], without any differences in 5-minute Apgar scores, arterial cord blood pH, neonatal transfer rates [25], neurologic abnormalities [16] or infant mortality [26] between vaginal breech delivery and planned cesarean section. However, these data were derived from smaller samples [16,25,26] or from multicentric trials [6].…”
Section: Discussionmentioning
confidence: 89%
“…Some have voiced their concerns about the reliability of the TBT data [14][15][16], criticizing the lack of adherence to the inclusion criteria, the variation in prenatal care consequent on the multicentric design, and the poor intrapartum fetal assessment that was not representative of conditions in the industrialized countries [17][18][19]. These reasons prompted suggestion that the recommendations of the TBT should be withdrawn [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'information donnée aux patientes n'insiste, sans doute, pas suffisamment sur le fait que cette augmentation du taux de césarienne ne s'accompagne pas d'une amélioration significative de l'état néonatal chez des enfants dont le tri par le score nous permet déjà d'assurer un bon pronostic. L'absence de différence de morbimortalité néonatale entre la naissance par voie vaginale ou par césarienne prophylactique a été observée dans l'étude PREMODA de même que dans d'autres séries [10][11][12][13]. L'évaluation du devenir à deux ans, des enfants inclus dans l'étude de Whyte et al, montre également l'absence de diffé-rence pour le développement moteur et cognitif quelle que soit la voie d'accouchement [14].…”
Section: Discussionunclassified
“…C'est volontairement que nous ne rentrerons pas dans cette problématique qui a très largement déjà été évoquée ailleurs [27,[49][50][51][52][53].…”
Section: Grossesse Gémellaire Avec J1 En Présentation Du Siègeunclassified